Environmental Risk Factors for Talaromycosis Hospitalizations of HIV-Infected Patients in Guangzhou, China: Case Crossover Study - Wang, Yaping; Deng, Kai (Frontiers in Medicine, 2021)
Talaromycosis is a fatal opportunistic infection prevalent in human immunodeficiency virus (HIV)-infected patients, previous studies suggest environmental humidity is associated with monthly talaromycosis hospitalizations of HIV-infected patients, but the acute risk factor remains uncertain. In this study, we evaluated the associations between talaromycosis hospitalizations of HIV-infected patients (n = 919) and environmental factors including meteorological variables and air pollutants at the event day (assumed “lag 0” since the exact infection date is hard to ascertain) and 1-7 days prior to event day (lag 1-lag 7) in conditional logistics regression models based on a case crossover design. We found that an interquartile range (IQR) increase in temperature at lag 0-lag 7 (odds ratio [OR] [95% CI] ranged from 1.748 [1.345-2.273] to 2.184 [1.672-2.854]), and an IQR increase in humidity at lag 0 (OR [95% CI] = 1.192 [1.052-1.350]), and lag 1 (OR [95% CI] = 1.199 [1.056-1.361]) were significantly associated with talaromycosis hospitalizations of HIV-infected patients. Besides, temperature was also a common predictor for talaromycosis in patients with co-infections including candidiasis (n = 386), Pneumocystis pneumonia (n = 183), pulmonary tuberculosis (n = 141), and chronic hepatitis (n = 158), while humidity was a specific risk factor for talaromycosis in patients with candidiasis, and an air pollutant, SO2, was a specific risk factor for talaromycosis in patients with Pneumocystis pneumonia. In an age stratified evaluation (cutoff = 50 years old), temperature was the only variable positively associated with talaromycosis in both younger and older patients. These findings broaden our understanding of the epidemiology and pathogenesis of talaromycosis in HIV-infected patients.